Pengaruh Pemberian Sari Tebu Terhadap Kadar Kolesterol Darah Pada Mencit - Rahma Widyastuti (Universitas Muhammadiyah Surabaya, 2017)
abstractSugarcane (Saccharum officinarum L.) is a plant known by the public as a refreshing drink that tastes sweet and the price is quite economical and readily available. Sugarcane contains octacosanol compounds that can lower cholesterol levels in the blood. Excessive cholesterol (hypercholesterolemia) a threat that is feared because as one of the causes of coronary heart disease (CHD) and stroke. The purpose of this study was to analyze the levels of cholesterol in mice, to analyze cholesterol levels in mice after the administration of sugar cane juice, to analyze the effect of sugar cane juice on cholesterol levels in mice. This type of research conducted by a group of experimental methods with populations of mice (Mus musculus) were obtained from farms Bojonegoro. The research sample selected by criteria mice aged 2-3 months, weighing between 20-40 grams of the male sex, the amount of sample used two groups of mice, each group consisted of 16 mice. From the results of blood cholesterol levels in mice after the administration of sugar cane juice, it is known that the average cholesterol level in the control group was 148.8750 mg / dl and value - average blood cholesterol treatment group was 118.2500 mg / dl. Statistically analyzed using a paired t test t value -3.799 obtained with significant value. (p) = 0.001 which is less than 0.05 then there is the effect (Ho is rejected) (t = -2.040 table). So we can conclude there is the effect of sugar cane juice on blood cholesterol levels in mice.Key word : Sugarcane, blood cholesterol levels